LP01–LP11Cross-Mode Interference in a Chirped Grating Inscribed in Two-Mode Fiber - Lim, Kok Sing; Islam, M.R.; Lee, Y.S.; Yang, H.Z.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2016)
We have demonstrated LP01-LP11 cross-mode interference in a single chirped grating (CG) inscribed in a two-mode fiber (TMF). With the aid of a binary phase plate, LP01 mode and LP11 mode can be selectively excited in the CG. By offsetting the position of the phase plate from the center of the input beam, we can simultaneously excite both the spatial modes at different LP01:LP11 intensity ratios in the TMF. The excited modes lead to the formation of different interference patterns in the output spectra. The measured output spectra are found to be in good agreement with the simulation based on a coupled mode theory.